Floating treatment wetland integrated with sediment microbial fuel cell for low-strength surface water treatment. (10th November 2022) - Shen, Shuting; Li, Xiang; Dai, Zheqin; Lu, Xiwu
Abstract: The combination of floating treatment wetland (FTW) and sediment microbial fuel cell (SMFC) has drawn increasing interest as an economical, effective, and environmentally sustainable method for energy recovery, remediation of contaminated sediments, and wastewater treatment. In this study, a novel FTW-SMFC system with vertical floating biocathodes was developed to evaluate the performance and mechanism of plants, substrates, and bio-electrochemical systems for treating low-strength surface water. Experiments were operated in batch mode and conducted in microcosms with the following six treatments: control system only containing water and sediment (CS), normal SMFC (SMFC), only plant system (PS), SMFC with plants (PSMFC), SMFC with substrates (S-SMFC), and SMFC with plants and substrates (S-PSMFC). The results show that introducing plants into SMFCs could increase the power density by 32.9–42.5%, proving that plants played an important role in enhancing bioelectricity production. The alkaline substrates reduced the cathode potential and made the cathode inefficient. The presence of plants and substrates greatly improved the removal of nitrogen and phosphorus. The removal efficiency of total nitrogen and total phosphorus increased by 8.3–27.8% and 3.5–13.9% under electrochemical treatment. There existed competition between electrochemical and plant removal approaches for nitrogen in FTW-SMFC, and electrochemical removal was prior to plant removal. Phosphorus removal was mainly through plant uptake and substrate-mediated adsorption and precipitation. The electrochemical process promoted the removal of phosphorus by enhancing the conversion of non-reactive phosphorus (NRP) to reactive phosphorus, providing 5.0–6.9% additional NRP conversion. This study furthers our understanding of the contribution and interaction of each component in the FTW-SMFC system to pollutant removal and bioenergy generation, which will contribute to the performance enhancement of FTW and further facilitate the application of FTW-SMFC technology for in-situ remediations of the polluted surface water body. Highlights: The contribution and interaction of components in FTW-SMFC were studied. Plants enhanced the power density by 33–43% while alkaline substrates lowered it. Increased current density promoted TN removal but limited TP removal. Electrogenesis limited nitrogen removal by plants but raised the RP use by plants. Electrogenesis provided 5.0–6.9% additional NRP conversion.